Design and fabricate a new concept recycle bin for general purpose - Wan Muhammad Azwan Fazley, Wan Ismail (2008)
This project is about designing and fabricating the recycle bin that can store rubbish such as can, glass and paper. To design and fabricated this recycle bin, it must be compare with other product that available in the market. First, get an idea from internet, magazine, newspaper or other from available data. Form there the information and idea to design and fabricated can be created. Whole project involves various methods such as collecting data, concept design and fabrication process. The whole project involved various method and process that usually use in engineering such as concept design, analysis process and lastly fabrication process. Overall from this project, time management and discipline is important to make sure this project goes smooth as plan and done at correct time.